Nurses' Organizational Commitment in Hospitals Affiliated to Tehran University of Medical Sciences - E Rahmanzade; Z Parsa Yekta; M Farahani; S Yekani Nejad (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: lack of organizational commitment of nurses would lead to low job performance and consequently result in deterioration of hospital care . The aim of this study is to determine the level of organizational commitment of nurses in the hospitals of Tehran University of Medical Sciences in 2014.   Material & Methods: It was a descriptive, cross- sectional study. The sample consisted of 262 nurses working in hospitals affiliated to Tehran University of Medical Sciences recruited by random stratified proportion to size sampling. Data was collected by demographic information form and the 24-item organizational commitment questionnaire of Allen and Meyer and analyzed by SPSS-PC (v. 17) using independent t-test, chi-square and ANOVA.   Results: Organizational commitment of most of the nurses (%80.9) was moderate. Among dimensions of commitment , the lowest score was related to normative commitment (%38.9) and the highest score was given to continuance commitment (%42.4). Organizational commitment was significantly correlated with age, work experience, employment and marital status (p<0.001).  Conclusion: Recognizing the dimensions and levels of organizational commitment of nurses to the organization provides an appropriate base for the decisions of organizations' managers in different levels of human resource management process.   Received: 10 Dec 2013   Accepted: 16 Feb 2014